Hydrogen Desorption from the NaNH2-MgH2 System - Sheppard, D; Paskevicius, Mark; Buckley, Craig (American Chemical Society, 2011)
Ball-milled sodium amide and magnesium hydride (NaNH2:MgH2 = 1:1 molar ratio) desorbs 3.3 wt % of hydrogen between 70 and 335 °C with three desorption events. X-ray diffraction indicates that the hydrogen desorption is associated with two unidentified magnesium-containing phases. Fourier transform infrared spectroscopy indicates that these two phases correspond to an imide and nitride, respectively. Analysis of the desorption products shows a large excess of NaH and MgH2 and that optimizing the starting reagents will increase both the kinetics and the amount of hydrogen desorbed from the system below 165 °C.